PENGARUH RISIKO AUDIT, UKURAN PERUSAHAAN, DAN MANAJEMEN LABA TERHADAP AUDIT FEE - Adelina Rizky Shafira; Imam Ghozali (Diponegoro Journal of Accounting, 2017)
This study aimed to examine the effect of audit risk, the size of the company, and the management of the Audit Fee income either directly or indirectly through audit fee on companies listed in the Indonesia Stock Exchange. Audit Fee is the amount of charge that can be affected by several factors where these factors can make the difference in fees paid by the company. This affects the performance of an auditor and have an impact on the quality of financial statements. The data used in this research is secondary data, that the financial statements and annual reports of 33 companies listed on the Indonesia Stock Exchange in 2012-2015. To prove the hypothesis, regression testing to see the effect immediately. However, before hypothesis test, performed classical assumption test which passed the regression model assumptions of classical test.The results showed audit risk, firm size, while management fee income has no effect on the audit fee.